TYPES OF POVERTY REDUCTION AND BASIC PRINCIPLES OF IMPLEMENTATION (Universal International Scientific Journal, 2026)
This article discusses the types of poverty reduction, their main priority features, and the main principles of their implementation. It also presents conclusions and suggestions for research on the types of poverty reduction and the main principles of their implementation.
Keywords: Poverty; income; poverty reduction